Influence of early melting of the ice cover and high water level on functioning of the coastal rookery for baikal seal (Pusa sibirica Gm.) on Dolgiy Island (Lake Baikal), on materials of 2020 - E. A. Petrov; A. B. Kupchinsky (Известия ТИНРО, 2023)
Functioning of a coastal seal rookery is considered on example of those located on Dolgiy Island in Lake Baikal, regularly visited by baikal seal Pusa sibirica Gm., which is constantly monitored by video surveillance. A case of the year 2020 with extremely early (comparing to 2011–2019) destruction and disappearance of ice in the northern part of the lake and rapid rise of the water level in summer-autumn is analyzed. Timing of the seals haul onshore and their abundance in rookery depend on the ice conditions: the lower ice cover – the earlier hauling-out and the higher abundance. Since the beginning of the rookery formation in May, up to 400 animals roosted there at the same time. Too early disappearance of the floating ice caused an abnormally large portion of individuals with incomplete molting on the rookery, and the delay in molting affected likely negatively on the animals health. Other negative factor was the deficit of available solid substrate for hauling-out because of rapid rise of the water level, particular in early summer. However, a large number of very well-fed adult females and males was observed on the rookery in May; presumably they did not participate in reproduction of population in 2020.